Applied Healthcare Knowledge Management for Hospital in Clinical Aspect - Sevenpri Candra; Ichsan Kurniawan Putrama (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Medical industry uses the information as a critical factor in running the three aspects of hospital management which includes administrative, financial and clinical. Objectives to be achieved is to identify healthcare knowledge resources and models of knowledge sharing, identifying culture, strategy and knowledge management supporting facilities, plotting knowledge resources and mapping supporting features of knowledge portals as well as doing analysis and design of healthcare knowledge management portal that developed.In achieving the purpose of analysis and design of healthcare knowledge management portal, is done through several stages of the methodology, where the identification process carried out primary and secondary data collection, while the analysis on the management aspects was performed cultural analysis with OCAI methods and the analysis and design of information systems with OOAD approach using UML models. PELNI Hospital is using for this case study. From analysis and design of healthcare knowledge management portal is expected to get a picture of the current organizational culture and the expected culture, the description of network infrastructure and organizational strategies related to resource and knowledge destination to produce a Knowledge Management Portal.